FAMILY AND COMMUNITY RESPONSIBILITY FOR EDUCATION - Amir Sahaka Sahaka (Jurnal Teknologi Pendidikan Madrasah, 2019)
Education is something that can not be separated from the lives of every human being, the quality of education obtained by a person since he was born and breathes fresh air in this world. There are three centers of education that must be experienced by children at least. 1. education in the family environment (informal), 2. education in the school environment (formal), and 3. education in the community (non-formal). The quality of education in Indonesia is currently considered by many to be of inferior quality, as an indicator of the quality of the Human Developman Index (Human quality index) is below other Southeast Asian countries such as Singapore, Thailand, and even Vietnam. There are several factors that cause the low quality of education in the country, among others: the learning process has not received optimal attention from the school, even the school has not become a center of learning and cultural center, the role of parents as primary and first educators especially to instill moral values, morals, virtues character, cultural, traditional and religious values ​​towards children, and no less important is the role of the community, as well as the role of Muslim clerics or scholars in implementing leadership or leadership in the life and relationships of Islam. Considering the task of educating children is not only the responsibility of the school or educational staff (formal), but it is the responsibility of both parents (family) as the primary and first (informal) educator and also the mandate which is carried on the shoulders of the murabbi (educators non-formal) which in the future Allah SWT will hold them accountable later on and will ask them what they have done as leaders. Actually each of us is a leader and one day we will be held accountable for our leadership (H.R. Bukhari Muslim).